Epidemiological profile of ameloblastoma affected patients subjected to surgery at a tertiary hospital in the state of Sao Paulo - Baldasserini, Gabriel Baldasserini; Scomparin, Leandro; M S de Freitas, Karina; Martins de Souza, Daniel Falbo; Cardoso, Renato; B Paredes, Wilber E (Revista Odontológica Mexicana, 2018)
Ameloblastoma is a locally invasive, odontogenic tumor of diffi cult early diagnosis. Treatment can vary from simple enucleation, enucleation associated to curettage and/or cryotherapy up to extensive surgical resections. The present study used epidemiological data of patients such as name, age, gender, type of ameloblastoma, region and type of treatment. Aforementioned data were collected from clinical histories of patients treated at the Mandaqui Hospital Compound during the period 01/01/2010 to 08/30/2016. Data were transcribed for the forms used every day in hospital, and were presented in tables and graphs. Out of 11 selected clinical histories, six patients were male and fi ve female, average age was 32 years. According to collected data, mandibular region was the most compromised (91%). Radiographically, the most frequently image was multilocular (64%), presence of singlecyst ameloblastoma was detected in four cases (36%). In three cases (27%) treatment consisted on decompression followed by curettage, in one case (9%) segmented resection was performed, in two cases (18%), segmented resection followed by reconstruction was achieved, in three cases (27%) enucleation followed by curettage, in two cases (18%), curettage and application of Carnoy solution. Maximum follow up period was fi ve years, no recurrence was observed in that period, nevertheless, there was follow up loss in these patients. Based on data obtained from studied population, it was concluded that average age varied from 10 to 66 years, mean age 32 years; on the other hand, male gender was the most compromised (55%), multilocular lesions were the most frequently found lesions (64%). Finally the most affected mandibular area was the posterior region of the lower jaw (73%), most frequent type of treatment was debridement (27%).